A Field Guide to North American Birders : a parody - Harmon, Margaret, frey50 (New York, N.Y. : Berkley Books, 2001)
Why watch a bunch of silly birds when you can watch a bunch of silly birdwatchers? That's the basis of this hilarious parody by Margaret Harmon.
Part III : Support for the serious Birder-watcher Getting serious - Birder-watching equipment - American Birder-watching Society (ABS) Code of Ethics - American birder-watching society decal - American Birder-watching Society's rules for counting birders - A birder-watcher's big year - Prevention of common birder-watching injuries - conservation note - North American checklist of the American Birder-watching society - field notes.
Keywords: Peterson, Roger Tory, -- 1908-; Birds -- Humor; Bird watchers -- Humor; Bird watching -- Humor